SINO-RUSSIAN COOPERATION AND ITS IMPACTS ON CENTRAL ASIA - Schutte, Giorgio Romano; Noveli Valadares, Diego (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
This article analyzes Sino-Russian cooperation in Central Asia, examining China’s growing economic presence and the reconfiguration of Russian influence in the region. Since 2014, Western sanctions and geopolitical tensions have led Moscow and Beijing to deepen their partnership. While China expands investments through the Belt and Road Initiative, Russia maintains its central role in regional security and financial influence. The study argues that despite China’s rise, Central Asia has become a space for strategic accommodation, where both powers avoid direct conflicts and consolidate their global presence.